2012
DOI: 10.1093/jrr/rrs122
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for respiratory motion management in radiation therapy

Abstract: Respiratory motion management (RMM) systems in external and stereotactic radiotherapies have been developed in the past two decades. Japanese medical service fee regulations introduced reimbursement for RMM from April 2012. Based on thorough discussions among the four academic societies concerned, these Guidelines have been developed to enable staff (radiation oncologists, radiological technologists, medical physicists, radiotherapy quality managers, radiation oncology nurses, and others) to apply RMM to radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 3 publications
0
31
0
Order By: Relevance
“…They can be classified into two major types [12]. One type of approach is to minimize the tumor motion using inhalation of oxygen, abdominal compression, learning of regular respiratory patterns, or a breath-hold technique [1316]. However, these methods are generally associated with modest efficacy and/or poor reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…They can be classified into two major types [12]. One type of approach is to minimize the tumor motion using inhalation of oxygen, abdominal compression, learning of regular respiratory patterns, or a breath-hold technique [1316]. However, these methods are generally associated with modest efficacy and/or poor reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…The gimbal mechanism enables tracing of tumor motion. [2][3][4] Electronic portal imaging devices (EPIDs), two sets of kilovolt x-ray tubes and flat panel detectors (FPDs), are mounted on the O-ring for IGRT. The Vero4DRT has many functionalities, including image-matching, 5D positional correction using a robotic couch, and real-time fluoroscopic monitoring during treatment.…”
Section: Introductionmentioning
confidence: 99%
“…One method by which to reduce the high dose to such organs is management of respiratory motion 5 , 6 . Several researchers have reported that pancreatic tumor motion due to breathing exceeded 10 mm using cine magnetic resonance images, four‐dimensional computed tomography (CT), electromagnetic transponders, and cone‐beam CT (CBCT) 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…(3,4) One method by which to reduce the high dose to such organs is management of respiratory motion. (5,6) Several researchers have reported that pancreatic tumor motion due to breathing exceeded 10 mm using cine magnetic resonance images, four-dimensional computed tomography (CT), electromagnetic transponders, and cone-beam CT (CBCT). (7)(8)(9)(10)(11)(12)(13)(14) Without respiratory management, a large planning target volume (PTV) is needed to cover such internal motion, resulting in inclusion of a large volume of OARs.…”
Section: Introductionmentioning
confidence: 99%